PENGARUH PENGALAMAN PPP, LINGKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI 2014 FE UNESA - DIAH RANI CANDRA SARI (Jurnal Pendidikan Ekonomi (JUPE), 2018)
Interests become teachears influenced by several factors, both internal and extern. The purpose of this research was to determine the influence of the partial and simultan of PPP experience, family environment and peers to interest become teachers. The population of this research was the student of economic education and by using Slovin obtained sample of 174 student. Methods of data collection using the questionnaires. Methods of data analysis using multiple linear regression analysis. The results showed simultaneously the experience of PPP, family environment and peers against the interest of becoming teachers of 56,7%. The results as partial, there is influence of PPP experience to the interest of becoming teacher equal to 23,42%, there family environment to the interest of become teacher equal to 23,17%, and there influence peer to interest become teacher equal 53,4%. Keywords: PPP experience, family environment, peers, and interest become teacher.